A recepção do livro didático de português e o processo de construção da competência leitora por alunos do Ensino Fundamental - Claudia Mara de Souza (2014)
This study assesses the reception process of the Portuguese textbook by elementary school II students in Reading. It attempts to answer the following questions: to what extent do students understand their own activities in reading and interpretation of texts in Portuguese textbooks? To what extent do they need the teachers intervention to understand the tasks? The initial hypothesis is that students fail to understand their reading activities and interpretation of texts proposed in the Portuguese textbook (LDP), they require the active participation of the teacher so as to understand the activities as well as to understand the text. The aim of this study is to investigate the extent to which elementary school students can understand on their own the reading activities and interpretation of texts from the Portuguese textbook and / or the extent to which understanding occurs when there is intervention. The specific objectives are: to determine the extent to which students understand the activities of the book; identify key questions shown by students in performing activities of reading; explain the relationship pupil / book with and without teacher mediation; point, with testimonials and interviews, the students' opinion about the textbook Portuguese; identify and list through the answers to the activities, which the reading skills students reveal and not reveal which possess at the end of the investigation.The research methodology used is qualitative and quantitative. Data collection is done in a public school in a municipality in Minas Gerais. The research corpus is composed of observed and filmed lessons, reading activities from the Portuguese textbook and answers to activities done, questionnaires to the students and interviews with teachers. Some classes are observed and filmed for verification of procedures and the class reactions during the performance of the activities. A reading activity from the textbook is given to four different groups in the class, with different strategies. Group A performs reading activities alone with no intervention; Group B performs the reading of the text with intervention and does the activities alone; group C performs the reading alone and does the activities with intervention; Finally group D performs the reading and the activities both with intervention. The proposed interventions were collaborative text reading, reading and review of the questions one by one. The answers to the activity are analyzed to determine what students can understand on their own and at which point they need mediation. Finally, students respond to a questionnaire in order to assess what they think about the Portuguese textbook, about the activities done on the texts, and teachers respond to the semi structured interview to verify their expectations, the approaches and what they think about the students needs and the necessary interventions.. The analysis is done in the light of theories that understand language as interaction, reading as a social and cognitive process of meaning production and the didactic intervention as the use of strategies for mobilizing capabilities to a level not yet achieved. The theoretical references are the authors Antunes (2003, 2010), Bakhtin ([1929]2006, [1952/1953] 1997), Marcuschi (2002), Cafiero (2010), Dell'Isola (2001), Kleiman (2004), Rojo (2003), Solé ( 1998) Vygotsky (1984,1991), among others. The results concerning analysis reveal that students have more difficulties in performing activities of textual interpretation when they have to do them alone. On the other hand, when there is a reading instruction, or when there`s intervention in the reading and activities, students` performance is superior. Furthermore, it is also noted that the reading activities present problems in their instructions, and the answers suggested in the teacher's manual of the textbook are not always consistent with the questions and / or sufficient for them, which makes their work more difficult. The student becomes hostage to his own limitations and constraints imposed by problematic activities from the textbook.